Neutrophilic leukocytosis and erythema nodosum leprosum in leprosy: insights from a retrospective observational study - Feitosa da Silva Barboza, Marcella; de Andrea Hacker, Mariana; Maria Sales, Anna; Fontoura Rodrigues, Débora; Pedrosa Marques, Daniel; José Ciryllo Silva Noya, Danillo; Leal Silveira Andrezo Rosa, Thabatta; de Fátima Alvim Braga, Isabel; Ferreira, Helen; Porto Amadeu, Thais; Gurgel de Oliveira, Monique; de Miranda Machado, Alice; et al. (Frontiers in Immunology, 2024)
Background Leprosy reactions represent immunologically mediated episodes of acute inflammation that, if not diagnosed and treated promptly, can cause irreversible impairment of nerve function and permanent disabilities. A frequent type of reaction experienced by patients with lepromatous leprosy (LL) and borderline lepromatous leprosy (BL) is erythema nodosum leprosum (ENL), an inflammatory complication that may become chronic or recur in multiple episodes. Although ENL is commonly described as a neutrophil-mediated immune disease, the role of neutrophils is not fully understood. In this study, we assess neutrophilic leukocytosis in a retrospective cohort of patients affected by BL or LL leprosy. Materials and methods A retrospective observational study was performed using data from 146 patients with BL and LL leprosy diagnosed and treated at the Souza Araújo Outpatient Clinic, Fiocruz, Rio de Janeiro, Brazil. Clinical, demographic, and hematological data were extracted from medical records. Skin biopsy samples obtained from patients for ENL diagnosis were used for histopathological evaluations. Results Most patients were male (75%) and had a reactional episode (85%), of which 65% were ENL. Multiple episodes were common, 55% of the 80 patients with ENL presented more than 2 episodes (average of 2.6 episodes). In treatment-naive BL/LL patients, the median blood neutrophil counts of patients who developed ENL at some points of their disease course were higher than those who did not experience any reaction (median= 4,567 cells/mm3 vs 3,731 cells/mm3 respectively, p=0.0286). A correlation between the increase in median neutrophil counts and ENL severity was confirmed (6,066 cells/mm3 for mild ENL vs 10,243 cells/mm3 for moderate/severe ENL, p=0.0009). A longitudinal assessment was also performed in 34 patients, confirming the neutrophilic leukocytosis (BL/LL: 4896 cells/mm3 vs ENL: 8408 cells/mm3, p<0.0001). Moreover, increased NLR was associated with a greater neutrophilic infiltration in ENL lesions. Conclusion We demonstrate that ENL episodes in patients affected by leprosy are associated with elevated blood leukocyte and neutrophil counts and an increased NLR. These findings highlight the significant involvement of neutrophils in the ENL immunological/inflammatory process.